Revolutionary War on Wednesday - Osborne, Mary Pope (Osborne, Mary Pope. Magic tree house series, 2000)
Using their magic tree house, Jack and Annie travel back to the time of the American Revolution and help General George Washington during his famous crossing of the Delaware River.